Developing Global Leaders through International Partnership: A Collaborative Model for Graduate Nursing Programs - Stephanie Gingerich; Gudrun Jonsdóttir; Jennifer Wentzel; Carol Flaten; Judy Pechacek; Helga Bragadóttir (Interdisciplinary Journal of Partnership Studies)
This paper presents a collaborative model for developing global leaders in graduate nursing programs, specifically through an international partnership between the University of Minnesota (UMN) and the University of Iceland (UI). The model, which relies on an innovative week-long immersion course, addresses the growing need for globally-minded nurse leaders capable of responding to the unique challenges of today's interconnected world. The immersive component included lectures, field trips, and a group project focused on the United Nations’ 17 Sustainable Development Goals. Evaluation data from the cohorts in the biannual programs in 2022 and 2024 (n=55) showed high satisfaction rates, with more than 90% of students rating the course as good or very good. Qualitative feedback highlighted themes of shared nursing experiences, a greater appreciation of global health-care systems, and the universal need for effective communication. The program aligned with competencies outlined by major nursing organizations. This model offers a promising approach for graduate nursing education to prepare leaders capable of addressing complex, interconnected global health challenges.